Rheological and Flow Behaviour of Yolk, Albumen and Liquid Whole Egg from Eggs of Six Different Poultry Species - Vojtěch Kumbár; Sylvie Ondrušíková; Daniel Trost; Adam Polcar; Šárka Nedomová (Foods, 2021)
Liquid egg products are one of the basic raw materials for the food industry. Knowledge of their rheological and flow behaviour in real technical elements is absolutely necessary for the selection of suitable technological equipment for their processing. In this article, the rheological properties of liquid egg products were determined. Eggs from six different species of poultry are used: domestic hen (Gallus gallus domesticus) hybrid Hisex Brown; Japanese quail (Coturnix japonica); German carrier goose (Anser anser f. domestica); domestic ducks (Anas platyrhynchos f. domestica); domestic guinea fowl (Numida meleagris f. domestica); and domestic turkeys (Meleagris gallopavo f. domestica). Liquid egg products showed pseudoplastic behaviour in range of shear strain rates from 0.2 up to 200 s−1 and at the temperature of 18 °C. Thus, the flow curves were constructed using the Ostwald-de Waele rheological model, with respect to the pseudoplastic behaviour of liquid egg products. According to the values of the coefficients of determination (R2), the sum of squared estimate of errors (SSE) and the root mean square error (RMSE), this model was appropriately chosen. Using the consistency coefficient K, the flow index n and the adjusted equations for the flow rate of technical and biological fluids in standard pipelines, the 3D velocity profiles of liquid egg products were successfully modelled. The values of the Reynolds number of the individual liquid egg products were calculated, and the type of flow was also determined. A turbulent flow has been detected for some liquid egg products.